The Influence of Service Quality and Worship Motivation on the Attendance of the Dawn Prayer Congregation at Masjid Al-Iman Sutorejo Surabaya - Isa Saleh; Abd Basith; Reka Gunawan (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2025)
This study aims to analyse the influence of Service Quality and Worship Motivation on the attendance of dawn prayer congregations at Al Iman Mosque in Surabaya, both individually and simultaneously. A quantitative approach was used with a survey method involving 70 congregants selected through purposive sampling. The data were analysed using Partial Least Squares (PLS) with the SmartPLS 4 application. The results showed that Service Quality did not have a significant effect on Congregation Attendance, with a p-value of 0.834 (>0.05), while Worship Motivation had a positive and significant effect on Congregation Attendance, with a p-value of 0.000 (<0.05). Simultaneously, both variables affect Congregation Attendance with an R-square value of 0.209, indicating that 20.9% of the variation in Congregation Attendance can be explained by Service Quality and Worship Motivation, while the rest is influenced by other factors outside the model. The limitations of this study lie in its scope, which only covers one mosque and focuses on congregants attending the dawn prayer, so the generalisation of the findings is still limited. Practically, the results of this study provide input for mosque managers to place greater emphasis on strengthening the spiritual motivation of congregants, not just on improving physical services. Socially, these findings show that strengthening ukhrawi values can be key to building sustainable religious participation in urban communities.